46.6k views
2 votes
M Solve the system. x - 2y + 2z = 9 y + 2z = 5 z = 3 Enter your answer as an ordered triple.

1 Answer

4 votes

Answer:

(1, -1, 3)

Step-by-step explanation:

The third equation says that z is equal to 3. So, we can replace this value on the second equation and solve for y as:


\begin{gathered} y+2z=5 \\ y+2(3)=5 \\ y+6=5 \\ y+6-6=5-6 \\ y=-1 \end{gathered}

Now, we can replace z by 3 and y by -1 on the first equation, so:


\begin{gathered} x-2y+2z=9 \\ x-2(-1)+2(3)=9 \\ x+2+6=9 \\ x+8=9 \\ x+8-8=9-8 \\ x=1 \end{gathered}

Therefore, the answer as an ordered triple is (x, y, z) = (1, -1, 3)

User Mike El Jackson
by
4.3k points